Comprehensive investigations on radiation shielding efficacy of bulk and nano Pb-Sn-Cd-Zn alloys. (1st May 2022) - Kaur, Taranjot; Vermani, Yogesh K; Al-Buriahi, M S; Alzahrani, Jamila S; Singh, Tejbir
Abstract: The alloys with composition: P b 60 S n 20 C d x Z n 20 − x, where x = 0, 5, 10, 15 and 20 mol . % were fabricated at nano-scale as well as bulk scale using the convention melt quench technique. Different characterization techniques such as Transmission Electron Microscopy (TEM), Field Emission-Scanning Electron Microscopy (FE-SEM) and Energy Dispersive Spectroscopy (EDS) analysis were performed to verify the particle size reduction to nano-scale, surface morphology and elemental composition of Pb60 Sn20 Cdx Zn(20-x) alloy systems. These nano-structured and bulk alloy systems were experimentally investigated and compared for their potential use in the radiation shielding applications. Further, radiation shielding effectiveness against electron beam, proton beam, alpha and heavy carbon ion beams has also been investigated for fabricated bulk alloys using Geant4 simulations. Present theoretical and experimental analysis affirmed that the radiation shielding efficacy gets enhanced for ball-milled PbSnCdZn nano alloy specimens as compared to bulk counterparts.